2016
DOI: 10.1080/2162402x.2016.1249090
|View full text |Cite
|
Sign up to set email alerts
|

T-helper cell receptors from long-term survivors after telomerase cancer vaccination for use in adoptive cell therapy

Abstract: We herein report retargeting of T-helper (Th) cells against the universal cancer antigen telomerase for use in adoptive cell therapy. The redirected Th cells may counter tumor tolerance, transform the inflammatory milieu, and induce epitope spreading and cancer senescence. We have previously conducted a series of trials evaluating vaccination with telomerase peptides. From long-term survivors, we isolated >100 CD4 C Th-cell clones recognizing telomerase epitopes. The clones were characterized with regard to HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
(104 reference statements)
3
11
0
Order By: Relevance
“…Studies in infectious disease have demonstrated that vaccines capable of producing polyfunctional T cell responses are highly effective, which emerging immunooncology studies have likewise suggested may be critical for effective anti-tumor immunity. [40][41][42][43][44][45] To investigate how LAMP trafficking may generate these enhanced responses, we focused on potential differences in MHC class I and II presentation and resulting CD4+ and CD8+ T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in infectious disease have demonstrated that vaccines capable of producing polyfunctional T cell responses are highly effective, which emerging immunooncology studies have likewise suggested may be critical for effective anti-tumor immunity. [40][41][42][43][44][45] To investigate how LAMP trafficking may generate these enhanced responses, we focused on potential differences in MHC class I and II presentation and resulting CD4+ and CD8+ T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based on the adoptive transfer of T cells that are genetically manipulated in order to express TCRs with high affinity for a given tumor antigen. TCR-engineered T cells designed to specifically recognize telomerase have been explored, but current data, although encouraging, are limited to pre-clinical experimental settings [108][109][110][111][112].…”
Section: Other Vaccination Approaches Targeting Htertmentioning
confidence: 99%
“…By comparison, the expression of TCR C13 and D71 in primary T cells after retroviral transduction is in our hands 30-60%. 25 As described, TCR D71 is consistently expressed at higher levels than C13 after mRNA transfection, even though the marker gene RQR8 is expressed at similar levels. The difference in expression between C13 and D71 thus appears to be inherent to the TCR.…”
Section: Discussionmentioning
confidence: 60%
“…23,24 We have previously reported the retroviral cloning and testing of two TCRs, called C13 and D71, against the hTERT-epitope GV1001. 25 Both C13 and D71 recognize peptides presented on DP4, which is the most prevalent HLA-molecule and expressed by >70% of Caucasians. 26 Their common HLA-restriction and the universal expression of hTERT suggest that these TCRs may be widely applicable in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%